Pemanfaatan Kecerdasan Buatan dalam Pengembangan Pasar E-commerce: Studi Kasus Chatbot dan Penerapan AI dalam Diagnostik Penuaan - Shefia Anggraeni; Binastya Anggara Sekti (Prosiding SISFOTEK, 2024)
The rapid advancement of technology has led to significant changes across various industry sectors, including e-commerce. The development of artificial intelligence (AI) in e-commerce is one such technology with a substantial impact. This research aims to explain the utilization of AI in e-commerce market development. By understanding how AI can address existing problems and create new opportunities, this study employs a literature review method to examine various relevant research and articles on the application of AI in e-commerce, with a particular focus on chatbots and aging diagnostics. The literature review method was chosen as the primary approach because it allows for the collection and analysis of data from various existing sources, providing a comprehensive overview of current trends and innovations in the field. This research uses a systematic literature review to analyze relevant studies and articles on AI applications in e-commerce, specifically focusing on chatbots and aging diagnostics. The literature review was selected as the main method because it enables the researcher to gather and analyze data from existing academic sources, offering a thorough understanding of current trends and innovations in the field. The research demonstrates that the use of artificial intelligence (AI) in e-commerce has a significant impact on market development and user experience.